PEMBUATAN DIES UAV J-1B DENGAN MOLD PENGECORAN METODE SAND CASTING - Wicaksono, Dhimas; Setiawan, ferry; Aditya Mahendra, Dimas; Satrya Buana, Allan; Qayyum, A; Endy Aditya, Virgiawan; Romadhon, Doni (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
Rapid technological advances, especially in the field of Unmanned Aerial Vehicles (UAV), have presented new challenges in the development of precision components. UAV, which can operate remotely or autonomously, require highly accurate components to ensure optimal performance and reliability. One important aspect in making UAV components is the casting process, where dimensional errors can affect the final performance of the UAV. This research aims to design and produce J-1B UAV Dies components using the sand casting method using used aluminum material. The research methodology carried out included experiments and observations, starting with 3D design using the SolidWorks application and continuing with making aluminum molds. During the casting process, it is known that the component size experiences significant shrinkage due to cooling of the molten metal, with a shrinkage percentage reaching 5.40% in the body section and 2.11% in the tail section. This shrinkage occurs due to changes in temperature which affect the volume of the metal when it hardens, as well as other factors such as removal of mold patterns and finishing processes which affect the final dimensions of the product. Variability in metal melting temperatures and casting techniques also contributes to product dimensional inaccuracies. This research emphasizes the importance of careful planning and strict quality control to minimize size differences and ensure conformity to the initial design. This research is fully funded by the STTKD campus, which is expected to equip the facilities and infrastructure for STTKD cadets in learning materials and support the development of UAV technology in the future.